Differential monocyte responses to TLR ligands in children with autism spectrum disorders - Enstrom, Amanda M (2009)
Autism spectrum disorders (ASD) are characterized by impairment in social interactions, communication deficits, and restricted repetitive interests and behaviors. Recent evidence has suggested that impairments of innate immunity may play an important role in ASD. To test this hypothesis, we isolated peripheral blood monocytes from 17 children with ASD and 16 age-matched typically developing (TD) controls and stimulated these cell cultures in vitro with distinct toll-like receptors (TLR) ligands: TLR2 (lipoteichoic acid; LTA), TLR3 (poly I:C), TLR4 (lipopolysaccharide; LPS), TLR5 (flagellin) and TLR9 (CpG-B). Supernatants were harvested from the cell cultures and pro-inflammatory cytokine responses for IL-1β, IL-6, IL-8, TNFα, MCP-1, and GM-CSF were determined by multiplex Luminex analysis. After in vitro challenge with TLR ligands, differential cytokine responses were observed in monocyte cultures from children with ASD compared with TD control children. In particular, there was a marked increase in pro-inflammatory IL-1β, IL-6 and TNFα responses following TLR2, and IL-1β response following TLR4 stimulation in monocyte cultures from children with ASD (p<0.04). Conversely, following TLR9 stimulation there was a decrease in IL-1β, IL-6, GM-CSF and TNFα responses in monocyte cell cultures from children with ASD compared with controls (p<0.05). These data indicate that, monocyte cultures from children with ASD are more responsive to signaling via select TLRs. As monocytes are key regulators of the immune response, dysfunction in the response of these cells could result in long-term immune alterations in children with ASD that may lead to the development of adverse neuroimmune interactions and could play a role in the pathophysiology observed in ASD.